Macroeconomics, nonlinearities, and the business cycle - Magnus Reif (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2019)
This dissertation focuses on describing and explaining business cycle dynamics. Motivated by the extraordinary strong economic downturn in 2008/2009, it emphasis the importance of modeling nonlinearities. This thesis should be regarded as a contribution to applied econometrics and can be clustered into two categories. The articles in chapter one and two take an applied stance by exploring different modeling strategies for the German economy. The articles in chapter three and four cover methodological contributions, especially with regard to economic forecasting. – – Im Zentrum dieser Dissertation steht das Beschreiben und Erklären von Konjunkturdynamiken. Motiviert durch den außerordentlich starken wirtschaftlichen Einbruch in 2008/2009 betont die Arbeit dabei die Wichtigkeit der Nutzung von nichtlinearen Modellansätzen. Die Dissertation kann als Beitrag im Bereich der angewandten Makroökonometrie gesehen werden und strukturiert sich in zwei Kategorien. Die Artikel in Kapitel eins und zwei bestehen aus angewandten Studien und untersuchen Modellansätze für die deutsche Wirtschaft. Die Artikel in den Kapiteln drei und vier bestehen aus methodischen Arbeiten insbesondere hinsichtlich ökonomischer Prognosen.
Keywords: C11; C53; C55; E31; E32; E37; E52; E58; 330; Forecasting; Nowcasting; Markov-Switching Dynamic Factor Model; BVAR; Threshold VAR; Time-Varying Parameter; Mixed-frequency Models; Bayesian Methods; Turning Points; Great Recession; Great Moderation; Counterfactuals; Stochastic 6556; Uncertainty